Optimization of Water Falling Points in Micro Hydro Power Plants - Hermawan, Heru; Sunardi, Sunardi (Universitas Ahmad Dahlan, 2021)
Micro Hydro Power Plant (PLTMH) is an alternative source of electrical energy for the community. PLTMH provides many benefits, especially for rural communities throughout Indonesia. When other energy sources start to run low and have a negative impact, water becomes a very important source of energy because it can be used as an energy source. PLTMH is a small-scale power plant that uses hydropower as its driving force such as irrigation channels, rivers, or natural waterfalls by utilizing the waterfall height (head) and the amount of water discharge. In rivers, there is the potential for sufficient water availability throughout the year, reliable discharge, suitable contours, and has been used for MHP. However, this river has decreased the electrical power it produces. Therefore, in this PLTMH river, it is necessary to analyze and recalculate the electric power generated by optimizing the water drop point, using an 8-inch pipe to produce a tangential force of 814.28 N, then using a 3-inch pipe to produce a tangential force of 100, 62 N and using a 2-inch pipe produces a tangential force of 25.37 N.